2018
DOI: 10.1186/s13020-018-0173-1
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin exerts neuroprotective effects by modulating the M1/M2 subset polarization of microglia/macrophages in the hippocampal CA1 region of vascular dementia rats via cannabinoid receptor 2

Abstract: BackgroundCerebral hypoperfusion is a pivotal risk factor for vascular dementia (VD), for which effective therapy remains inadequate. Persistent inflammatory responses and excessive chemotaxis of microglia/macrophages in the brain may accelerate the progression of VD. Endocannabinoids are involved in neuronal protection against inflammation-induced neuronal injury. Cannabinoids acting at cannabinoid receptor 2 (CB2R) can decrease inflammation. Based on the identification of paeoniflorin (PF) as a CB2R agonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 39 publications
2
60
0
Order By: Relevance
“…However, persistent and excessive inflammatory responses can aggravate tissue injury, lead to chronic inflammation, and thereby prevent the routine process of tissue repair. To reduce inflammation and promote wound healing in the later stage of inflammation, macrophages are transformed into an M2 phenotype by an alternative activation pathway and secrete anti-inflammatory cytokines, such as Arg-1, IL-4, IL-10, transforming growth factor-β1, and Ym1 [ 17 , 19 , 26 , 27 ]. Therefore, the dynamic equilibrium between M1 and M2 macrophages is vital for wound healing and tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, persistent and excessive inflammatory responses can aggravate tissue injury, lead to chronic inflammation, and thereby prevent the routine process of tissue repair. To reduce inflammation and promote wound healing in the later stage of inflammation, macrophages are transformed into an M2 phenotype by an alternative activation pathway and secrete anti-inflammatory cytokines, such as Arg-1, IL-4, IL-10, transforming growth factor-β1, and Ym1 [ 17 , 19 , 26 , 27 ]. Therefore, the dynamic equilibrium between M1 and M2 macrophages is vital for wound healing and tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniflorin, an active ingredient in a traditional Chinese medicine, was reported to be a CB2R agonist that modulates the M2 phenotype evidenced by an increase in M2 markers, including Arg1, Ym1, IL-10, and TGF-β1, and a decrease in M1 markers, including IL-1β, IL-6, and TNFα, in a middle cerebral artery occlusion (MCAO) model. These modulatory effects were reversed by co-treatment with AM630 (109). However, it is unknown whether this compound is a CB2R agonist, despite its ability to increase CB2R expression.…”
Section: Microglial Polarization By Ecb In Cerebral Hemorrhage and Stmentioning
confidence: 99%
“…Actually, from a therapeutic point of view, targeting CB 1 has poor prospects due to the widespread distribution in brain and in both neurons and glia, to the psychotropic properties of agonists (phytocannabinoids or synthetic CB 1 R agonists) and also due to the side effects occurring after administration to humans of rimonabant, a selective CB 1 R ligand (Sam, Salem, & Ghatei, ). Recently it has been demonstrated that activation of CB 2 R by paeoniflorin, one of the major constituents of Paeonia lactiflora , regulates the polarization of microglia/macrophages in hippocampus (CA1 region) in vascular dementia models, (Luo et al, )). In conclusion, our data support the view that, via microglia, A 2A R antagonists may enhance the action of cannabinoids in CB 2 R and the final output is neuroprotective.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been demonstrated that activation of CB 2 R by paeoniflorin, one of the major constituents of Paeonia lactiflora, regulates the polarization of microglia/macrophages in hippocampus (CA1 region) in vascular dementia models, (Luo et al, 2018)). In conclusion, our data support the view that, via microglia, A…”
Section: Discussionmentioning
confidence: 99%